The world of Nali's poetry - سعید, محمد احمد; ئەحمەد, تریفه محەمەد (Sulaimani Journal for Humanities, 2025)
This research is entitled the ‘World of Naali’s Poetry’. This is a summery of a section in a thesis for Masters degree in Kurdish literature, under the name ‘The Rational of Existence and Nonexistence in Naali’s Poetry’. It is a descriptive and explanatory research with the objective of getting to know his poems while it aims at filling another gap about the poet in particular and within Kurdish literature in general, considering that Naali was a great famous Baban poet who alongside Saalim and Kurdi helped prospering the literature of Kirmanji xwaru and the Slemani part of Kurdish literature. Our research consists of three parts : In the first part, we highlighted his poetry and the work of the orientalists, local and foreign writers and researchers who wrote about Naali. In the second part, we focussed on Naali’s philosophy and poetry. We elaborated on subjects like vocabulary and specific expressions related to philosophy, myth and religious contents, in addition to rejecting injustice and criticizing some of the cultural norms and habits through utilisation of his poetry which aimed at delivering his message and expressing his perspectives. He also had the goal of deeply observing humans and society. As for the third section, we have discussed Islam religion in relation to Naali’s personal worshipping where he described the greatness of god and the prophet, despite of writing some pieces in which he criticized dervishand Sofiism phenomenon Each section in the research includes many examples of poems